2018
DOI: 10.1111/hel.12479
|View full text |Cite
|
Sign up to set email alerts
|

Th‐17 response and antimicrobial peptide expression are uniformly expressed in gastric mucosa of Helicobacter pylori‐infected patients independently of their clinical outcomes

Abstract: This study showed that CXCL-8, IL-17A, and AMPs are not differently expressed according to the various H. pylori -related diseases. The clinical outcome determinism of H. pylori infection is most likely not driven by gastric inflammation but rather tends to mainly influenced by bacterial virulence factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Adamsson et al reported that the level of expression of the genes encoding the prototype Th17 cytokine IL‐17A and the Th1 lymphokine IFN‐γ is enhanced in the corpus and antrum of Swedish patients with H. pylori infection compared to uninfected individuals; more importantly they confirmed by immunofluorescence that the number of IL‐17A + and IFN‐γ + cells is also increased in H. pylori ‐infected patients . Similar to that, a significant increase in IL17A mRNA transcripts was observed in the gastric tissue of H. pylori ‐infected patients from Iran and France compared to uninfected ones. Arachchi et al also reported that H. pylori infection is associated with elevated IL‐17 serum concentrations in a human cohort from Sri‐Lanka .…”
Section: Immunologymentioning
confidence: 71%
See 2 more Smart Citations
“…Adamsson et al reported that the level of expression of the genes encoding the prototype Th17 cytokine IL‐17A and the Th1 lymphokine IFN‐γ is enhanced in the corpus and antrum of Swedish patients with H. pylori infection compared to uninfected individuals; more importantly they confirmed by immunofluorescence that the number of IL‐17A + and IFN‐γ + cells is also increased in H. pylori ‐infected patients . Similar to that, a significant increase in IL17A mRNA transcripts was observed in the gastric tissue of H. pylori ‐infected patients from Iran and France compared to uninfected ones. Arachchi et al also reported that H. pylori infection is associated with elevated IL‐17 serum concentrations in a human cohort from Sri‐Lanka .…”
Section: Immunologymentioning
confidence: 71%
“…However, two studies showed that the number of infiltrating Th17 cells is higher in H. pylori ‐infected patients with peptic ulcers compared to individuals with H. pylori gastritis . To converse, Cremniter et al described that the same level of IL17A mRNA is found in patients with gastritis, ulcer, or precancerous and cancerous lesions …”
Section: Immunologymentioning
confidence: 99%
See 1 more Smart Citation
“…To extrapolate quantitative results for biopsies, a standard curve for PCR was implemented using ten-fold geometric serial dilutions (1 × 10 −1 to 1 × 10 −7 ) of a CFU-numbered suspension of a 48 h-cultured H. pylori J99-type strain [ 28 , 29 ]. Presence of H. pylori was determined by detecting the glmM gene specific for this bacterial species.…”
Section: Methodsmentioning
confidence: 99%
“…The amount of eCFU was numbered using the calibration curve. Absence of PCR inhibitors was assessed by detection of a 110-bp-long fragment of a human housekeeping gene (β-globin) [ 28 ].…”
Section: Methodsmentioning
confidence: 99%